KADAR HEMOGLOBIN DAN PREVALENSI ANEMIA PADA IBU LAKTASI YANG BEKERJA DAN YANG TIDAK BEKERJA - Rahayu Astuti; Agustin Syamsianah (JURNAL LITBANG, 2005)
Background : Nutritional anemia among lactating mothers is the one of nutritionalproblem in Indonesia , indicated by the decreasing of hemoglobin level. Lactating mothers can get the nutritional anemia because of blood losses on partus. Objective : to discover hemoglobin level and anemia prevalence on lactating working mothers and lactating non working mothers. Method : this research design is analytical research with cross sectional approach. The research location is in "Kelurahan Ngemplak Simongan, Kecamatan Semarang Barat, Kota Semarong". All the samples are 86 lactating mothers, divided into two groups that are 49 (57,0 %) lactating working mothers and 37 (43,0 %) lactating non working mothers. The data collected by interview method that are respondent identity and the frequency of food consumption. Hemoglobin level analyze by Sianmethemoglobine method. Result : The amount of (95,9 %) lactating working mothers are industrial workers and 4,1 % are government workers. The average of hemoglobin level on lactating working mothers is 10,8 gr %, but on lactating non working mothers is 11,2 gr  %. Anemia prevalence among the lactating working mothers is 65,3 % but on lactating non working mothers is 37,8 %. Conclusion : There is a significant dffirence of the average hemoglobin level between the lactating working mothers and the lactating non working mothers (p value = 0,009). There is a significant difference of the anemia prevalence between the lactating working mothers and the lactating non working mothers (p value = 0,011). Key words : hemoglobin level, anemia,lactating mothers, Junral Litbang